Antibacterial Activities from Gel Hand Sanitizer of Jatropha curcas Leaves Ethanolic Extract Against Staphylococcus aures ATCC 25923 - Erviana Vernanda Margaretha; Yohanes Juliantoni; Dyke Gita Wirasisya (Universitas Mataram, 2020)
Food borne disease is a disease with symptoms such as nausea, diarrhea and vomiting. The main cause of FBD was food contamination of Staphylococcus aureus. Jarak pagar (Jatropha curcas Linn) leave is a plant that have antibacterial activity against S. aureus because it contains saponin, flavonoid, and tannin. This research aimed to determine the antibacterial activity of the ethanolic extract of Jatropha curcas Linn. leaves, formulated them as gel hand sanitizer, and evaluated the antibacterial activity of the formula. The sample was collected, determined, and extracted with ethanol 70% using maceration, and the phytochemical screening conducted to the concentrate extract. The antibacterial activity test conducted by well diffusion method with concetration 50, 100, dan 150 mg/mL. Then the effective extract group has formulated to gel hand sanitizer. The gel hand sanitizer formula tested the antibacterial activity and physical properties by organoleptic, pH, stability, and spreadablility. The result showed that the extract with concentration 50, 100, dan 150 mg/mL has inhibition zone diameter was 9.9, 15.7, and 16.4 mm, respectively. The gel hand sanitizer of Jatropha curcas Linn extract was formulated by using 100 mg/mL concentration of extract. The gel was physically stable and had inhibition zone diameter was 15.6 mm